Observed tidal currents on the continental shelf off the east coast of India. (1st June 2017) - Jithin, A.K.; Unnikrishnan, A.S.; Fernando, V.; Subeesh, M.P.; Fernandes, R.; Khalap, S.; Narayan, S.; Agarvadekar, Y.; Gaonkar, M.; Tari, P.; Kankonkar, A.; Vernekar, S.
Abstract: In the present study, we analysed 9-month long data from Acoustic Doppler Current Profilers (ADCP) deployed on the shelf off the east coast of India to study the characteristics of tidal currents in the region. The ADCPs were deployed at about 100–150 m depths off Cuddalore (CD, 12.0°N), Ramayapatnam (RM, 15.0°N), Kakinada (KN, 16.3°N) and South of Gopalpur (SG, 18.6°N). Tidal currents in the region are mainly semidiurnal in nature and dominant constituent is M2 . Semimajor axes of barotropic tidal ellipses of M2 is about 1.9 cms −1 in the southernmost ADCP location (off CD) and it is about 4.0 cms −1 in the northernmost ADCP location (off SG), which indicate a northward increase of tidal currents. Baroclinic spectra show high energy at tidal frequencies, which suggests the presence of internal tides on the shelf, particularly in the semidiurnal band. Semidiurnal internal tides of about 8–15 cms −1 are observed at different locations and the magnitude is relatively large on the shelf off SG in the northern part of the shelf, which is primarily due to large barotropic forcing on the north. The semidiurnal internal tides are found to be intensified at the bottom, particularly on the shelf off SG and RM. The computed ratio of slope of internal wave characteristics ( c ) and topographic slope (γ) indicates that large near-critical regions present surrounding the ADCP locations off SG and RM could be the possible reason of bottom intensification at these two locations. EOF analysis shows that observed semidiurnal internal tides are dominated by the first baroclinic mode, where it accounts for about 70–80% of semidiurnal internal tide variability on the shelf off SG and CD, whereas the contribution of the first mode is relatively small (43–50%) on the shelf off KN and RM. Enhanced small-scale vertical shear is observed at the ADCP locations associated with multimode structure of semidiurnal internal tides. Semidiurnal internal tides show a spring-neap variability on the shelf off SG and CD, whereas they are highly incoherent and intermittent on the shelf off RM and KN. Temporal variability of semidiurnal internal tide magnitude on the shelf is mainly due to the change in stratification, which is explained based on monthly climatology data. Highlights: Characteristics of barotropic and internal tides on continental shelf off the east coast of India are described. Semidiurnal internal tides are energetic in the northern part of the shelf. Enhanced vertical shear associated with multimodal structure of semidiurnal internal tides. Semidiurnal internal tides are bottom intensified and seasonal variability is explained by the stratification.